PERANAN VISUM ET REPERTUM YANG DI BUAT OLEH DOKTER NON FORENSIK SEBAGAI ALAT BUKTI DALAM TINDAK PIDANA PENGANIAYAAN (Studi Kasus Putusan Nomor 1180K/Pid/2014): Kurniawan - admin, admin (Reformasi Hukum, 2018)
Vindication in a criminal act of persecution by the investigators needed help experts namely doctors of justice (forensic) or other doctors to perform Visum Et Repertum toward patients or sacrifice. The purpose of the forensic examination in the case of abdominal ulceration is to know the type of wound, type of violence and the degree of the wound. Cases of criminal act such as the persecution is one of the examples of cases where the investigators very need assistance experts, including medical experts of justice (forensic doctors). In practice Visum Et Repertum does not only issued by the forensic doctor or specialist doctors medicine judicial authority only, but also issued a doctor non forensic. Approach method used in this bachelor theses is the normative research method, which researchers discuss the theories in science literature skunder. This research aims to find out whether Visum Et Repertum made by the doctor non forensic can be used as evidence in the criminal procedural law in Indonesia, How the role of the Visum Et Repertum made by non doctors as evidence forensic act of persecution in the decision (No. 1180 K/Pid/2014), and how an overview of Islamic law menngenai evidences. From the results of research can be deduced that in the Decree of the Minister of Justice No M. 01.PW.07-03 1982 about KUHAP Guidelines in explaining the Article 133 paragraph (2) about perbendaan Visum Et Repertum results issued by the forensic doctors and doctors non forensic, in the explanation to the information from the doctor is not an expert in medicine of justice (non-doctors) forensic as a ketereangan experts but the description itself can be an indication and that the instructions are valid evidences. And the making of Visum done non doctors as there are forensic verdict MA No. 1180 K/Pid/2014 needed re-examination by the doctor forensic as Medicolegal Field (consultant medical science and knowledge of the law to have a high value Visum results that made the doctor non forensic.